Improved model‐free adaptive predictive control‐based cooperative driving control for connected and automated vehicles subject to time‐varying communication delays and packet losses at signal‐free intersections. Issue 10 (18th September 2022) - Yu, Jie; Jiang, Fachao; Luo, Yugong; Kong, Weiwei
Abstract : The cover image is based on the Research Article Improved model‐free adaptive predictive control‐based cooperative driving control for connected and automated vehicles subject to time‐varying communication delays and packet losses at signal‐free intersections by Jie Yu et al., https://doi.org/10.1049/itr2.12222 .